Aksesibilitas dan Literasi Digital Musisi Independen dalam pemanfaatan Platform Distribusi Musik Believe Backstage - Rengga Ramayuda; Soni Reffali; Hinhin Agung Daryana (Institut Seni Indonesia Denpasar, 2025)
Purpose: This study analyzes the experiences of the independent band AidoAudio in utilizing the digital music distribution platform Believe Backstage. The purpose is to examine how digital accessibility and digital literacy affect the band's ability to manage releases, interpret analytics, and implement promotional strategies. This focus aims to uncover the challenges and opportunities faced by Indonesian independent musicians in the digital music ecosystem. Method: This study employs a qualitative method with an instrumental case study strategy. Data were collected through semi-structured interviews with band members, supported by documentation including dashboard screenshots, official tutorials, and pitching forms. Data analysis used thematic coding to identify patterns related to accessibility and digital literacy. Triangulation and member checking ensured data credibility. Result and Discussion: The analysis shows that AidoAudio has strong operational-technical literacy, allowing smooth release uploads and compliance with metadata standards. However, interpretative and strategic literacy, including analytics use and editorial pitching, remains limited. Administrative barriers at the early access stage require attention but do not directly block platform use. The interplay between accessibility and literacy indicates that effective digital distribution depends not only on platform availability but also on the band’s internal capacity to build legitimacy, manage informal channels, and leverage social networks. Implication: This study highlights the importance of multidimensional digital literacy for independent musicians, emphasizing that access without literacy results in partial utilization, whereas literacy without formal access does not ensure effective distribution. The findings provide a model for optimizing digital music distribution strategies in Indonesia.